Արևելյան լեգեոնը և Ֆրանսիայի քաղաքականությունը թուրքական նոր հրապարակումների լույսի ներքո - Հովհաննիսյան, Անուշ («Զանգակ - 97»)
The article is analyzing developments regarding the Eastern (Armenian) Legion in the period between 1917 and April 1918, based on the documents provided from the French State Archives and recently published in Turkey. The documents show that some tensions arose from the requests of some leading prominant Armenians wanting to join the Legion. The correspondence demonstrates double-faced policy of French administration, wanting to have an offensive force ready for attack with the plans of France on the one hand, from the other hand concerning about the influence of those Armenians over soldiers and trying to prevent possible actions of Legion to the own interest of Armenians.
Keywords: Պատմություն; Քաղաքականություն